Metodologia para cálculo da temperatura de cor e fluxo luminoso de um ou mais LEDs baseada apenas em dados do fabricante - Bolzan, Thaís Ertmann (2020)
This work presents a methodology to estimate the correlated color temperature and the luminous flux of light sources composed of one or more white LEDs using only data from the manufacturer's specification sheet. The methodology was proven through experimental tests with seven LEDS with color temperature of 4000K and seven of 6500K. The LEDs were powered individually, at two different ambient temperatures (25ºC and 35ºC) and also together. All tests were performed with four current values (25%, 50%, 75% and 100% of the rated current). The values calculated according to the methodology were compared with values measured in the experimental tests in relation to power, junction temperature, chromaticity coordinate, correlated color temperature and luminous flux. The results found were satisfactory, with a maximum error of 2.08% for correlated color temperature and 5.05% for luminous flux. The developed methodology was then applied to a system, aiming to meet the non-visual aspects of lighting and to contribute to human well-being through the adaptation of lighting to the circadian cycle. In this system, through an app, it is possible to vary both the correlated color temperature and the luminous flux of a lamp, according to the user's desire. Two lamps were developed and tested, the first with a color temperature variation from 4100K to 6500K and luminous flux from 250 lm to 1200 lm and the second with color temperature variation from 2700K to 6500K and luminous flux from 300 lm to 1180 lm. 20 white LEDs of two different color temperatures were used in each lamp. Both systems presented adequate performance, with maximum error between values defined by the user in the app and measured of 3.48% for correlated color temperature and 10% for luminous flux.